Clinical and laboratory correlation of dermatophytic infection in patients in tertiary care hospital - Smita Damke; Deevanshi Rathore (Journal of Krishna Institute of Medical Sciences University, 2022)
Background: Dermatophytosis is caused by a homogenous group of keratinophilic fungi called dermatophytes that have the capacity to invade keratinized tissue i.e. skin, hair and nails of humans and animals. Fungal infections do not receive much attention and are diagnosed very late as they are not notifiable, unlike viral, bacterial, and parasitic diseases. Aim and Objectives: To identify and characterize different species of dermatophytes from clinically diagnosed cases of ringworm infections. Material and Methods: Characterization was based upon the morphological features in direct Potassium Hydroxide (KOH) mount, growth on Sabouraud Dextrose Agar (SDA) and Dermatophyte Test Medium (DTM) for primary isolation of dermatophytes from clinical samples. Results: In the present study, total of 176 samples were collected. Causative agents were identified macroscopically and microscopically from the growth obtained from SDA. Out of the 176 patients from whom samples were collected, males were found to be more common, with the male to female ratio being 2:1. Most common clinical type was Tinea cruris (39.20%) followed by Tinea corporis (30.11%). Most common fungal isolate was Trichophyton rubrum followed by Trichophyton mentagrophytes. Thus, it was observed that although mycological culture gives a definitive diagnosis, it is time consuming. Conclusion: Combined use of KOH mount and culture growth should be used for proper and definitive diagnosis of dermatophytosis.